Change in the spectrum of detected mutations in the DMD gene depending on the methodological capabilities of the laboratory - E. V. Zinina; M. V. Bulakh; O. P. Ryzhkova; O. A. Shchagina; A. V. Polyakov (Нервно-мышечные болезни)
Background. Duchenne muscular dystrophy (DMD) is a severe, progressive form of muscular dystrophy that occurs in children between one and three years of age. The disease is mainly characterized by weakness of the proximal muscles, which leads to difficulty in movement, and ultimately to complete disability. Becker muscular dystrophy (BMD) is a milder allelic form of the disorder characterized by late onset and slow progression. The cause of the development of DMD/BMD is mutations in the DMD gene, leading to a deficiency in the production of various isoforms of the dystrophin protein family. The most common mutations in case of DMD/BMD are gross deletions (55–65 %) and duplications (6–11 %) of one or several exons The remaining cases of DMD/BMD are due to small mutations (approximately 20–30 %). Depending on the methodological capabilities of the laboratory, the idea of the spectrum of mutations in the DMD gene changed, which is important in genetic counseling of patients and planning the therapy available today.Aim. To analyze the spectrum of mutations in the DMD gene, including three time slices, depending on the methodological capabilities of the laboratory.Materials and methods. We analyzed the spectrum of mutations in the DMD gene for a sample of 2957 patients admitted to the laboratory of DNA diagnostics of the Research Centre for Medical Genetics with a referral diagnosis of DMD/BMD. Depending on the time of treatment and the capabilities of the laboratory, patients were divided into three groups: 2008–2015, 2016–2018, 2019–2022.Results. As a result of the study, the full range of mutations in the DMD gene was analyzed over three-time intervals, which makes it possible to get an idea of the distribution of mutation types in the sample among Russian patients. Regardless of the methodological capabilities of the laboratory, the spectrum of mutations in the DMD gene remains biased relative to world data. At the moment, there is a significant decrease in the proportion of extended deletions (50.7–59.6 %), while the proportion of extended duplications (11.8–17.2 %) and small mutations (23.2–35.0 %) increased. We assume that the main reason for such features of the spectrum is ethnic and population differences.Conclusion. Duchenne/Becker muscular dystrophy (DMD/BMD) is the most common form of muscular dystrophy, accounting for more than 50 % of all cases. Determination of the spectrum of mutations provides an understanding of their frequencies, which in the future may help patients in the appointment of therapy specific to a particular type of mutation.